Positive electrode active material and method for producing same, self-supporting electrode film and method for producing same, positive electrode, battery, and power-driven device

CN123017922APending Publication Date: 2026-10-30ZHANJIANG POWER SUPPLY BUREAU OF GUANGDONG POWER GRID CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611181369.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,传统湿法工艺存在以下缺陷:(1)需使用NMP等有毒有机溶剂,环保成本高且存在安全隐患;(2)高温干燥过程中易引发粘结剂迁移和粉体团聚,导致电极孔隙分布不均、界面阻抗增加

Benefits of technology

[0047]本申请利用氧化锆以及氧化铝的复合包覆对磷酸铁锂颗粒进行表面改性,复合包覆层有效增强了磷酸铁锂颗粒的机械强度以及结构稳定性,同时采用球形改性剂对磷酸铁锂颗粒进行球形化改性,显著提高了颗粒的球形度以及流动性,减少了干法工艺高剪切过程中细粉的产生,使改性后的活性材料能够良好地适配干法电极的成膜工艺。此外,本申请采用复合包覆以及球形化改性相结合的策略对磷酸铁锂颗粒进行协同改性,复合包覆层与球形化结构协同作用,保障了电极结构的均匀性以及一致性,提升了电池的循环稳定性以及倍率性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017922A_ABST
    Figure CN123017922A_ABST
Patent Text Reader

Abstract

The application provides a positive electrode active material and a preparation method thereof, a self-supporting electrode film and a preparation method thereof, a positive electrode, a battery and an electric device. The preparation method of the positive electrode active material comprises the following steps: providing a precursor solution, wherein the precursor solution comprises an aluminum salt and a zirconium salt; mixing lithium iron phosphate with the precursor solution, drying, and preparing a pretreated material, wherein the total mass of aluminum and zirconium in the precursor solution accounts for 0.6% to 1.8% of the mass of the lithium iron phosphate; mixing the pretreated material with a spherical modifier, grinding and sintering, and preparing a positive electrode active material. The application adopts a strategy of combining composite coating and spherical modification to synergistically modify lithium iron phosphate particles, and the composite coating layer and the spherical structure synergistically act to guarantee the uniformity and consistency of the electrode structure and improve the cycle stability and rate performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of cathode material technology, and in particular to a cathode active material and its preparation method, a self-supporting electrode film and its preparation method, a cathode, a battery, and an electrical device. Background Technology

[0002] With the continuous development of new energy vehicles and large-scale energy storage industries, higher technical demands are being placed on the energy density, cycle life, and industrialization cost of lithium-ion batteries. Lithium iron phosphate (LFP) has become one of the most promising candidate materials for lithium-ion battery cathodes due to its advantages such as high safety performance, long cycle life, low cost, and environmental friendliness.

[0003] Currently, the preparation of LFP electrodes is still mainly based on wet processes, which involves dispersing active materials, conductive agents, and binders in organic solvents such as N-methylpyrrolidone (NMP) to form a slurry, which is then coated, dried, rolled, and cut to obtain electrode sheets. However, traditional wet processes have the following drawbacks: (1) they require the use of toxic organic solvents such as NMP, resulting in high environmental costs and safety hazards; (2) the high-temperature drying process can easily cause binder migration and powder agglomeration, leading to uneven electrode pore distribution and increased interfacial impedance.

[0004] Although traditional dry electrode technology eliminates organic solvents, the compatibility of existing dry processes with LFP materials is still insufficient: traditional LFP particles have low mechanical strength and poor flowability, and are prone to breakage and fine powder production during the high-shear dry process, affecting electrode consistency; at the same time, the commonly used PTFE binder has insufficient bonding force with LFP particles, and is prone to delamination during long-term cycling; in addition, single high-pressure rolling can easily lead to membrane brittleness and uneven porosity distribution, resulting in poor electrode consistency and deterioration of electrochemical performance. Summary of the Invention

[0005] Based on this, this application provides a positive electrode active material with good fluidity and electrochemical performance, a method for preparing the same, a self-supporting electrode film and a method for preparing the same, a positive electrode, a battery, and an electrical device.

[0006] This application provides a method for preparing a positive electrode active material, including the following steps:

[0007] A precursor solution is provided, the precursor solution comprising an aluminum salt and a zirconium salt;

[0008] Lithium iron phosphate is mixed with the precursor solution and dried to prepare a pretreated material, wherein the total mass of aluminum and zirconium in the precursor solution accounts for 0.6% to 1.8% of the mass of lithium iron phosphate.

[0009] The pretreated material is mixed with a spherical modifier, and then ground and sintered to prepare a positive electrode active material.

[0010] In one embodiment, one or more of the following conditions are met:

[0011] (1) The molar ratio of aluminum to zirconium in the precursor solution is (1.5~2.5):1;

[0012] (2) The spherical modifier includes one or more of polyethylene glycol, polypropylene glycol, and polyethylene wax;

[0013] (3) The mass of the spherical modifier is 1% to 5% of the mass of the lithium iron phosphate;

[0014] (4) The grinding speed is 2000 r / min~3000 r / min;

[0015] (5) The grinding time is 2 h to 6 h;

[0016] (6) The sintering temperature is 600 ℃~700 ℃;

[0017] (7) The sintering time is 4 h to 8 h;

[0018] (8) The aluminum salt includes one or more of aluminum nitrate, aluminum chloride, aluminum sulfate, and aluminum acetate;

[0019] (9) The zircon salt includes one or more of zirconium nitrate, zirconium chloride, zirconium oxychloride and zirconium acetate.

[0020] This application also provides a positive electrode active material prepared according to the above preparation method.

[0021] Furthermore, this application also provides a method for preparing a self-supporting electrode film, comprising the following steps:

[0022] A dry powder mixture is prepared by mixing the above-mentioned positive electrode active material, polyurethane binder, and conductive agent.

[0023] The dry powder mixture is subjected to shearing and at least two pressing processes to prepare the self-supporting electrode film;

[0024] The polyurethane adhesive is a cross-linked product of polyol and aliphatic polyisocyanate trimer.

[0025] In one embodiment, one or more of the following conditions are met:

[0026] (1) The mass ratio of the active material, the polyurethane adhesive and the conductive agent is (92~96):(1~3):(2~5);

[0027] (2) The conductive agent includes one or both of graphene and Super P;

[0028] (3) The shearing temperature is 50 ℃~90 ℃;

[0029] (4) The cutting time is 8 min to 12 min;

[0030] (5) The shearing speed is 600 r / min to 1800 r / min;

[0031] (6) The pressure of the first pressing is 80 MPa~120 MPa;

[0032] (7) The temperature for the first pressing is 20 ℃~30 ℃;

[0033] (8) The pressure of the second pressing is 150 MPa~180 MPa;

[0034] (9) The temperature for the second pressing is 80 ℃~100 ℃;

[0035] (10) The polyol includes one or both of polyether polyol and polyester polyol;

[0036] (11) The aliphatic polyisocyanate trimer includes one or both of hexamethylene diisocyanate trimer and isophorone diisocyanate trimer;

[0037] (12) The polyol and the aliphatic polyisocyanate trimer are mixed and heated to 70 ℃~90 ℃ to prepare the polyurethane adhesive;

[0038] (13) The mass ratio of the polyol to the aliphatic polyisocyanate trimer is (85~92):(8~15).

[0039] Furthermore, this application also provides a self-supporting electrode film, which is prepared according to the above-described method for preparing a self-supporting electrode film.

[0040] In one embodiment, the self-supporting electrode film satisfies one or more of the following conditions:

[0041] (1) Thickness is 60 μm~180 μm;

[0042] (2) Porosity is 35%~45%;

[0043] (3) The compacted density is 3.7~4.0 g / cm³. 3 .

[0044] This application also provides a positive electrode, including a current collector and a self-supporting electrode film as described above disposed on one or both surfaces of the current collector.

[0045] This application also provides a battery, including a positive electrode as described above.

[0046] This application also provides an electrical device, including the battery described above.

[0047] This application utilizes a composite coating of zirconium oxide and alumina to modify the surface of lithium iron phosphate particles. The composite coating effectively enhances the mechanical strength and structural stability of the lithium iron phosphate particles. Simultaneously, a spherical modifier is used to spherize the lithium iron phosphate particles, significantly improving their sphericity and flowability, reducing the generation of fine powder during the high-shear process of dry processing, and enabling the modified active material to be well-suited for dry electrode film formation. Furthermore, this application employs a combined strategy of composite coating and spherical modification to synergistically modify the lithium iron phosphate particles. The composite coating and the spherical structure work together to ensure the uniformity and consistency of the electrode structure, improving the battery's cycle stability and rate performance. Attached Figure Description

[0048] Figure 1 This is a scanning electron microscope image of the surface of the electrode obtained in Example 1 of this application;

[0049] Figure 2 This is a scanning electron microscope image of the surface of the electrode prepared in Comparative Example 1 of this application;

[0050] Figure 3 The first charge-discharge curve of the electrode prepared in Example 1 of this application at a rate of 0.1 C is shown.

[0051] Figure 4 This is a graph showing the cycling performance of the electrode prepared in Example 1 of this application at a rate of 1.0 C. Detailed Implementation

[0052] To facilitate understanding of this application, it may be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application.

[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.

[0054] In this document, unless otherwise stated, "one or more" means any one of the listed items or any combination of the listed items. Similarly, "one or more" and other instances of "one or more" are to be understood in the same way unless otherwise stated.

[0055] In this document, terms such as "further," "even further," "especially," "for example," "like," "example," and "exemplary" are used for descriptive purposes to indicate a connection in the coverage of different technical solutions presented earlier and later. However, they should not be construed as limitations on the preceding technical solution or on the scope of protection of this document. Unless otherwise specified, in this document, A (e.g., B) indicates that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0056] In this document, "optionally," "optionally," and "optional" mean that something is optional, that is, it is selected from either "present" or "absent." If multiple "options" appear in a technical solution, unless otherwise specified and there are no contradictions or mutual constraints, each "option" is independent. In this application, descriptions such as "optionally contains" and "optionally includes" indicate "contains or does not contain." "Optional component X" indicates whether component X exists or does not exist, or whether component X is contained or not.

[0057] In this document, the terms "first aspect," "second aspect," "third aspect," and "fourth aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," and "fourth" serve only as a non-exhaustive enumeration and should be understood as not constituting a closed limitation on quantity.

[0058] In this article, the technical features described in an open-ended manner include both closed technical solutions composed of the listed features and open technical solutions that include the listed features.

[0059] In this document, when referring to numerical intervals (i.e., numerical ranges), unless otherwise specified, the distribution of selectable values ​​within a numerical interval is considered continuous, and includes the two endpoints (i.e., the minimum and maximum values) of the numerical interval, as well as every value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all subranges included therein. The "numerical value" in this numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include percentage intervals, ratio intervals, proportion intervals, and other numerical interval types.

[0060] This application provides a method for preparing a positive electrode active material, comprising the following steps: providing a precursor solution containing aluminum salt and zirconium salt; mixing lithium iron phosphate with the precursor solution, drying, and preparing a pretreated material, wherein the total mass of aluminum and zirconium elements in the precursor solution accounts for 0.6% to 1.8% of the mass of lithium iron phosphate; mixing the pretreated material with a spherical modifier, and then grinding and sintering to prepare an active material.

[0061] This application utilizes a composite coating of zirconium oxide and alumina to modify the surface of lithium iron phosphate particles. The composite coating effectively enhances the mechanical strength and structural stability of the lithium iron phosphate particles. Simultaneously, a spherical modifier is used to spherize the lithium iron phosphate particles, significantly improving their sphericity and flowability, reducing the generation of fine powder during the high-shear process of dry processing, and enabling the modified active material to be well-suited for dry electrode film formation. Furthermore, this application employs a combined strategy of composite coating and spherical modification to synergistically modify the lithium iron phosphate particles. The composite coating and the spherical structure work together to ensure the uniformity and consistency of the electrode structure, improving the battery's cycle stability and rate performance.

[0062] Specifically, the aluminum salt in the precursor solution may be, but is not limited to, one or more of aluminum nitrate, aluminum chloride, aluminum sulfate, and aluminum acetate; the zirconium salt may be, but is not limited to, one or more of zirconium nitrate, zirconium chloride, zirconium oxychloride, and zirconium acetate. The aluminum and zirconium salts dissolve in deionized water to form a homogeneous precursor solution, which is beneficial for achieving uniform coating on the surface of lithium iron phosphate particles.

[0063] Specifically, the total mass ratio of aluminum and zirconium elements in the precursor solution to the mass of lithium iron phosphate can be, but is not limited to, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, or 1.8%. When the coating amount is below 0.6%, the composite coating layer is too thin, resulting in limited mechanical reinforcement of the lithium iron phosphate particles, and fine powder is still easily generated during the dry high-shear process. When the coating amount is above 1.8%, the coating layer is too thick, which may lead to increased particle agglomeration, thereby reducing powder flowability. At the same time, an excessively thick coating layer increases the ion transport distance, which is detrimental to rate performance. Within the range of 0.6% to 1.8%, the composite coating layer can achieve a good balance between enhancing particle strength and maintaining ion transport efficiency.

[0064] In some specific examples, the molar ratio of aluminum to zirconium in the precursor solution is (1.5~2.5):1.

[0065] Specifically, the molar ratio of aluminum to zirconium can be, but is not limited to, 1.5:1, 1.7:1, 1.9:1, 2.0:1, 2.1:1, 2.3:1, or 2.5:1. The molar ratio of aluminum to zirconium has a significant impact on the microstructure and properties of the composite coating. When the proportion of aluminum is too high (molar ratio > 2.5:1), the Al2O3 content in the coating is too high, resulting in higher hardness but increased brittleness, making it prone to microcracks during cycling. When the proportion of zirconium is too high (molar ratio < 1.5:1), the ZrO2 content is too high, resulting in better toughness but insufficient hardness, weakening the mechanical protection effect on the particles. Within a molar ratio range of (1.5~2.5:1), the hardness provided by Al2O3 and the toughness provided by ZrO2 work synergistically to form a composite coating with both high strength and good toughness, effectively resisting mechanical impacts in dry processes and volumetric deformation during cycling.

[0066] Specifically, the spherical modifier can be, but is not limited to, one or more of polyethylene glycol, polypropylene glycol, and polyethylene wax. When polypropylene glycol is selected, its average molecular weight is controlled between 400 and 2000, preferably 1000. It can completely decompose and volatilize during the high-temperature sintering stage, without introducing impurities into the lithium iron phosphate system, effectively smoothing particle edges and improving powder sphericity and flowability. Among them, polyethylene glycol (PEG) plays a role in lubricating and assisting in rounding the edges of particles during the grinding process, reducing sharp corners and breakage, improving powder flowability, and completely decomposes and volatilizes during subsequent high-temperature sintering without introducing impurities, making it a preferred spherical modifier.

[0067] Specifically, the mass ratio of the spherical modifier to the lithium iron phosphate mass can be, but is not limited to, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%. When the amount of spherical modifier is less than 1%, the lubrication effect is insufficient, and the degree of rounding of the particle edges is limited; when the amount is more than 5%, the excessive modifier may generate a large amount of gas during sintering, resulting in a loose and porous coating layer, reducing the density and protective effect of the coating layer.

[0068] Specifically, the grinding speed can be, but is not limited to, 2000 r / min, 2100 r / min, 2200 r / min, 2300 r / min, 2400 r / min, 2500 r / min, 2600 r / min, 2700 r / min, 2800 r / min, 2900 r / min, or 3000 r / min. The grinding speed directly affects the degree of rounding of the particle edges and the uniformity of the coating layer. When the speed is below 2000 r / min, the grinding energy is insufficient, the degree of rounding of the particle edges is limited, and the improvement in powder flowability is not significant. When the speed is above 3000 r / min, the excessive mechanical impact energy may cause the lithium iron phosphate particles to break, resulting in more fine powder, which is not conducive to subsequent dry film formation. Within the range of 2000 r / min to 3000 r / min, effective rounding of the particle edges can be achieved without damaging the particle body.

[0069] Specifically, the grinding time can be, but is not limited to, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, or 6 h. The grinding time and grinding speed work together to determine the degree of particle sphericity. If the grinding time is too short (<2 h), the modification effect will be insufficient; if the grinding time is too long (>6 h), it may lead to over-grinding and the generation of fine powder, while reducing production efficiency.

[0070] Specifically, the sintering temperature can be, but is not limited to, 600 ℃, 620 ℃, 640 ℃, 650 ℃, 660 ℃, 680 ℃, or 700 ℃. The selection of the sintering temperature needs to consider several factors: on the one hand, the temperature needs to be high enough to allow the precursor salt to fully decompose into the corresponding oxide and form a dense coating layer; on the other hand, the temperature cannot exceed the upper limit of the thermal stability of lithium iron phosphate (approximately 750 ℃), otherwise it will lead to the destruction of the lithium iron phosphate crystal structure and the degradation of electrochemical performance. Within the range of 600 ℃ to 700 ℃, the precursor salt can fully decompose and form a dense coating layer without damaging the crystal structure of lithium iron phosphate.

[0071] Specifically, the sintering time can be, but is not limited to, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, or 8 h. The sintering time and sintering temperature work together to determine the crystallinity and density of the coating layer. If the sintering time is too short (<4 h), the precursor salt will not decompose completely, resulting in a loose and non-dense coating layer; if the sintering time is too long (>8 h), it may lead to excessive growth of lithium iron phosphate grains, reducing the rate performance of the material.

[0072] In some specific examples, the method for preparing a self-supporting electrode film includes: mixing the above-mentioned positive electrode active material, polyurethane binder and conductive agent to prepare a dry powder mixture; subjecting the dry powder mixture to shearing and at least two pressing processes to prepare a self-supporting electrode film; wherein the polyurethane binder is a crosslinking product of polyol and aliphatic polyisocyanate trimer.

[0073] In some specific examples, the mass ratio of positive electrode active material, polyurethane binder, and conductive agent is (92~96):(1~3):(2~5). Specifically, the mass percentage of positive electrode active material can be, but is not limited to, 92%, 93%, 94%, 95%, or 96%. The mass percentage of polyurethane binder can be, but is not limited to, 1%, 1.5%, 2%, 2.5%, or 3%. The mass percentage of conductive agent can be, but is not limited to, 2%, 3%, 4%, or 5%. When the proportion of positive electrode active material is less than 92%, the energy density of the electrode is low; when it is higher than 96%, the amount of binder and conductive agent is insufficient to construct a complete three-dimensional cross-linked network and conductive pathway, and the mechanical strength and conductivity of the electrode film will decrease. When the proportion of polyurethane binder is less than 1%, the three-dimensional cross-linked network is incomplete, the electrode film lacks flexibility and is prone to cracking; when it is higher than 3%, too much binder will coat the surface of the positive electrode active material, hindering the transport of lithium ions.

[0074] In some specific examples, the conductive agent includes one or both of graphene and Super P. Specifically, the conductive agent can be, but is not limited to, graphene, Super P, or a combination of both. Graphene is a two-dimensional sheet-like carbon material with extremely high electrical conductivity and excellent mechanical strength; a small amount of graphene can construct an efficient electron transport network between active material particles. Super P is a common conductive carbon black with a well-developed branched structure and a high specific surface area, capable of filling the tiny gaps between active material particles, forming a complementary conductive network with graphene. The combined use of graphene and Super P can achieve a complete electronic conduction pathway with a relatively low amount of conductive agent.

[0075] In some specific examples, polyols include one or both of polyether polyols and polyester polyols.

[0076] In some specific examples, aliphatic polyisocyanate trimers include one or both of hexamethylene diisocyanate trimers and isophorone diisocyanate trimers.

[0077] In some specific examples, the mass ratio of polyol to aliphatic polyisocyanate trimer is (85~92):(8~15). Specifically, the mass ratio can be, but is not limited to, 92:8, 90:10, 88:12, 86:14, or 85:15. The polyol provides the main chain structure that constitutes the three-dimensional cross-linked network, and the aliphatic polyisocyanate trimer acts as a cross-linking agent. The multiple isocyanate groups contained in its molecule undergo an in-situ cross-linking reaction with the hydroxyl end groups of the polyol to construct a continuous fibrous adhesive network. When the mass percentage of aliphatic polyisocyanate trimer is less than 8% (i.e., the mass ratio of the two is greater than 92:8), the amount of crosslinking agent is insufficient, the crosslinking point density between the prepolymer molecular chains is low, making it difficult to form a complete and continuous three-dimensional crosslinked network. This results in insufficient mechanical strength of the self-supporting electrode film and insufficient bonding force with the current collector, making it prone to demolding, powdering, or film delamination during dry film formation. When the mass percentage of aliphatic polyisocyanate trimer is greater than 15% (i.e., the mass ratio of the two is less than 85:15), the crosslinking density is too high, the crosslinking network is too rigid, and the flexibility is significantly reduced, making the electrode film brittle and prone to cracking. Furthermore, excessive isocyanate groups may undergo side reactions in subsequent processes or the electrolyte environment, affecting interfacial stability. Controlling the mass ratio of the two within the range of (85~92):(8~15) ensures the integrity and continuity of the three-dimensional crosslinked network while also considering the flexibility and mechanical strength of the electrode film. This is beneficial for dry shear fibrillation and subsequent roll forming, and reduces the electrode / electrolyte interfacial impedance.

[0078] In some specific examples, polyurethane adhesives are prepared by heating a mixture of polyols and aliphatic polyisocyanate trimers to 70 ℃~90 ℃. When the crosslinking temperature is below 70 ℃, the crosslinking reaction rate is too slow, the degree of crosslinking is insufficient within a limited residence time, and the chemical stability of the fiber network decreases. When the temperature is above 90 ℃, the crosslinking reaction is too fast, which may lead to local over-crosslinking and a decrease in the uniformity of the fiber network.

[0079] In some specific examples, the shearing temperature is 50℃~90℃. Specifically, the shearing temperature can be, but is not limited to, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, and 90℃. The shearing temperature includes a preheating zone of 50℃~60℃, a cross-linking zone of 70℃~90℃, and a fibrillation zone of 80℃~90℃. Within the cross-linking zone, the polyurethane adhesive undergoes a thermally initiated in-situ cross-linking reaction, and simultaneously forms nanoscale fibers under shear force, constructing a three-dimensional cross-linked adhesive network to obtain a fibrous material.

[0080] In some specific examples, the shearing time is 8 to 12 minutes. The shearing time can be, but is not limited to, 8, 9, 10, 11, or 12 minutes. If the shearing time is too short, crosslinking and fibrillation will be insufficient; if it is too long, it may lead to polyurethane degradation.

[0081] In some specific examples, the shearing speed is 600 r / min to 1800 r / min. The shearing speed can be, but is not limited to, 600 r / min, 700 r / min, 800 r / min, 900 r / min, 1000 r / min, 1100 r / min, 1200 r / min, 1300 r / min, 1400 r / min, 1500 r / min, 1600 r / min, 1700 r / min, or 1800 r / min. If the speed is too low, the shear force is insufficient to achieve adequate fibrillation; if it is too high, it may cause fiber breakage.

[0082] In some specific examples, the pressure of the first compression is 80 MPa to 120 MPa. Specifically, the pressure of the first compression can be, but is not limited to, 80 MPa, 90 MPa, 100 MPa, 110 MPa or 120 MPa.

[0083] In some specific examples, the temperature of the first pressing is 20 ℃ to 30 ℃. The temperature of the first pressing can be, but is not limited to, 20 ℃, 25 ℃ or 30 ℃.

[0084] In some specific examples, the pressure of the second compression is 150 MPa to 180 MPa. The pressure of the second compression can be, but is not limited to, 150 MPa, 160 MPa, 170 MPa or 180 MPa.

[0085] In some specific examples, the temperature of the second pressing is 80 ℃ to 100 ℃. The temperature of the second pressing can be, but is not limited to, 80 ℃, 85 ℃, 90 ℃, 95 ℃, or 100 ℃. The first pressing is carried out at room temperature to initially densify the powder particles; the second pressing is carried out at a high temperature to further densify the particles, so that the porosity and thickness of the electrode film meet the target requirements.

[0086] When the first pressing pressure is below 80 MPa, the powder particles are not sufficiently densified, making it difficult to form a self-supporting film; above 120 MPa, the film may become brittle. When the second pressing pressure is below 150 MPa, the densification is insufficient; above 180 MPa, the porosity is too low, affecting electrolyte wetting. When the second pressing temperature is below 80 ℃, the polyurethane has insufficient fluidity and poor densification effect; above 100 ℃, it may lead to excessive cross-linking or degradation of the polyurethane.

[0087] The thickness of the self-supporting electrode film is 60 μm to 180 μm; specifically, the thickness of the self-supporting electrode film can be, but is not limited to, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, or 180 μm. The porosity is 35% to 45%; specifically, the porosity of the self-supporting electrode film can be, but is not limited to, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, or 45%. The compacted density is 3.7 g / cm³. 3 ~4.0 g / cm 3 The compaction density of the self-supporting electrode film can be, but is not limited to, 3.7 g / cm³. 3 3.8 g / cm 3 3.9 g / cm 3 Or 4 g / cm 3 .

[0088] In some specific examples, the positive electrode includes a current collector and the aforementioned self-supporting electrode film disposed on one or both surfaces of the current collector.

[0089] Specifically, the current collector can be, but is not limited to, aluminum foil, copper foil, or aluminum foil with a pre-coated carbon layer. In the pre-coated carbon layer aluminum foil, the carbon layer thickness can be, but is not limited to, 1 μm, 1.5 μm, or 2 μm. The function of the pre-coated carbon layer is twofold: firstly, the rough surface structure of the carbon layer increases the contact area between the current collector and the electrode film, enhancing the mechanical anchoring effect; secondly, the carbon layer has good conductivity, which reduces the interfacial contact resistance between the current collector and the electrode film. Furthermore, the carbon layer can form a stronger interfacial bond with the polyurethane adhesive during hot pressing, further improving the adhesion between the electrode and the current collector.

[0090] In some specific examples, the battery includes the aforementioned positive electrode. Specifically, the battery can be a lithium-ion battery. The negative electrode sheet of the battery can use conventional negative electrode materials such as graphite and silicon-carbon, the electrolyte can use conventional lithium-ion battery electrolyte, and the separator can be made of polyethylene, polypropylene, or a composite separator thereof.

[0091] In some specific examples, the electrical device includes the aforementioned battery.

[0092] Specifically, the electrical device may be, but is not limited to, electric vehicles, power tools, energy storage power stations, consumer electronic devices, etc. The following detailed description, in conjunction with specific embodiments, further illustrates this application.

[0093] It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application. For experimental methods in the following embodiments where specific conditions are not specified, please refer to the guidelines given in this application, or follow experimental manuals or conventional conditions in the field, or follow the conditions recommended by the manufacturer, or refer to experimental methods known in the field.

[0094] In the specific embodiments described below, the measurement parameters involving raw material components may have slight deviations within the weighing accuracy range unless otherwise specified. Temperature and time parameters are subject to acceptable deviations due to instrument testing accuracy or operational precision.

[0095] The components of the self-supporting electrode film, by mass percentage, are: 94% modified lithium iron phosphate active material, 3% composite conductive agent (graphene and Super P mixed at a mass ratio of 1:4), and 3% polyurethane binder (polyols compounded in a 1:1 ratio of polyether-type polyols and polyester-type polyols mixed with hexamethylene diisocyanate trimer at a mass ratio of 88:12, and thermally crosslinked at 70~90 ℃). The current collector is made of aluminum foil with a pre-coated carbon layer, the carbon layer thickness is about 1.5 μm, and 0.8% of polyolefin hot melt adhesive by mass of the carbon layer is added to the carbon layer.

[0096] Example 1

[0097] Take 100 parts by mass of lithium iron phosphate powder, add 2 parts by mass of Al-Zr nitrate aqueous solution precursor, the Al / Zr molar ratio in the precursor is 2:1, and the total mass of Al and Zr metal accounts for 1.0% of the LFP powder. After thorough mixing, vacuum dry to obtain the coated pretreated material. Add 1 part by mass of polyethylene glycol-4000 spherical modifier to the pretreated material and put it into a high-speed ball mill. Grind at 2500 r / min for 3 h. The ball-milled powder is transferred to a sintering furnace and sintered at 650 ℃ for 6 h. After cooling, pass through a 200-mesh sieve to obtain Al2O3-ZrO2 composite coated and spherically modified lithium iron phosphate active material.

[0098] The above-mentioned active materials, the composite conductive agent of graphene and Super P in a 1:4 ratio, and the cross-linked polyurethane binder were added to a high-speed dry mixer at a mass ratio of 94:3:3. The mixture was first mixed at a low speed of 600 r / min for 6 min, and then the speed was increased to 1800 r / min for 12 min of high-shear dry mixing. The temperature was controlled at 40 ℃ throughout the process to obtain a uniform dry powder mixture. The dry powder was then fed into a twin-screw shear with a length-to-diameter ratio of 45:1. The temperatures of the preheating zone, cross-linking zone, and fibrillation zone were set to 55 ℃, 80 ℃, and 85 ℃, respectively. The shearing speed was 1000 r / min and the total shearing time was 10 min to obtain a fibrous powder composite.

[0099] The fibrous powder composite was fed into a multi-roller continuous press. First, a cold pressing was performed at 25 ℃ room temperature and 100 MPa pressure to initially form a self-supporting membrane. Then, a second hot pressing was performed at 90 ℃ and 160 MPa pressure to control the membrane thickness and porosity, ultimately yielding a membrane with a thickness of 120 μm, a porosity of 40%, and a compacted density of 3.80 g / cm³. 3 A self-supporting electrode film.

[0100] Example 2

[0101] The difference from Example 1 is that only the amount of coating precursor solution added was adjusted: only 1 part by mass of precursor solution (total metal mass of Al and Zr accounting for 0.6% of LFP) was added to 100 parts of lithium iron phosphate powder, while all other process parameters remained the same. The final product had a thickness of 135 μm, a porosity of 43%, and a compaction density of 3.72 g / cm³. 3 A self-supporting electrode film.

[0102] Example 3

[0103] The difference from Example 1 is that in the dry powder mixing step, the modified lithium iron phosphate, composite conductive agent, and biodegradable crosslinked polyurethane binder are mixed in a ratio of 95:3:2. The final product has a thickness of 128 μm, a porosity of 42%, and a compacted density of 3.75 g / cm³. 3 A self-supporting electrode film.

[0104] Example 4

[0105] The difference from Example 1 is that in the temperature gradient shearing step, the three temperature zones of the twin-screw shear were adjusted to a preheating zone of 50°C, a cross-linking zone of 75°C, and a fibrillation zone of 80°C. The final product had a thickness of 142 μm, a porosity of 44%, and a compaction density of 3.70 g / cm³. 3 A self-supporting electrode film.

[0106] Example 5

[0107] The difference from Example 1 is that polyethylene glycol-4000 was replaced with polypropylene glycol-1000. The final product had a thickness of 145 μm, a porosity of 46%, and a compacted density of 3.45 g / cm³. 3 A self-supporting electrode film.

[0108] Comparative Example 1

[0109] The difference from Example 1 is that unmodified lithium iron phosphate powder was used as the active material. The final product had a thickness of 145 μm, a porosity of 44%, and a compacted density of 3.60 g / cm³. 3 Self-supporting electrode film. For example... Figure 1 The image shown is a scanning electron microscope (SEM) image of the surface of the electrode prepared in Example 1 of this application; Figure 2 This is a scanning electron microscope image of the surface of the electrode prepared in Comparative Example 1 of this application.

[0110] Comparative Example 2

[0111] The difference from Example 1 is that, in the preparation steps of the active material, aluminum nitrate and zirconium nitrate precursors are not added. Instead, lithium iron phosphate powder is mixed with polyethylene glycol-4000 at a mass ratio of 100:1, followed by ball milling and sintering. That is, only spheroidization modification is performed without composite coating. The final product has a thickness of 140 μm, a porosity of 42%, and a compaction density of 3.60 g / cm³. 3 A self-supporting electrode film.

[0112] Comparative Example 3

[0113] The difference from Example 1 is that in the preparation steps of the active material, polyethylene glycol-4000 is not added; instead, lithium iron phosphate powder is simply mixed with the precursor and then ball-milled and sintered. That is, only composite coating is performed without spheroidization modification. The final product has a thickness of 132 μm, a porosity of 45%, and a compacted density of 3.52 g / cm³. 3 A self-supporting electrode film.

[0114] Comparative Example 4

[0115] The difference from Example 1 is that the biodegradable crosslinked polyurethane adhesive was replaced with an equal amount of PTFE adhesive, and the twin-screw shearing process was carried out at room temperature without a temperature gradient. The final result was a thickness of 148 μm, a porosity of 43%, and a compaction density of 3.65 g / cm³. 3 A self-supporting electrode film.

[0116] Comparative Example 5

[0117] The difference from Example 1 is that the precursor solution contained only zirconium nitrate. The final product had a thickness of 138 μm, a porosity of 42%, and a compacted density of 3.66 g / cm³. 3 A self-supporting electrode film.

[0118] Comparative Example 6

[0119] The difference from Example 1 is that the precursor solution contained only aluminum nitrate. The final product had a thickness of 134 μm, a porosity of 45%, and a compacted density of 3.58 g / cm³. 3 A self-supporting electrode film.

[0120] Battery assembly and electrochemical performance testing

[0121] The self-supporting electrode film prepared in this application was hot-pressed onto the surface of a pre-coated carbon-aluminum foil current collector, and then subjected to secondary rolling and cutting to obtain a dry-process positive electrode. Using a lithium metal sheet as the counter electrode, a 1 mol / L LiPF6 solution of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (volume ratio 3:7) was used as the electrolyte, with 1% fluoroethylene carbonate (FEC) added. A polypropylene (PP) porous membrane was used as the separator, and CR2032 coin cells were assembled in an argon-filled glove box. The electrochemical performance of the coin cells was tested using a Blue Battery testing system, with a test voltage range of 2.2–4.2 V and a test temperature of room temperature. The performance data are shown in Table 1 below. Figure 3 The figure shown is the first charge-discharge curve of the electrode prepared in Example 1 of this application at a rate of 0.1 C; as shown Figure 4 The figure shown is a cycle performance diagram of the electrode prepared in Example 1 of this application at a rate of 1.0 C.

[0122] Table 1

[0123]

[0124] Analysis of experimental results:

[0125] As shown in Table 1, the initial discharge specific capacity at 0.1 C, initial coulombic efficiency, and capacity retention rate after 300 cycles at 1.0 C in Example 1 are all superior to those in Examples 2-5 and Comparative Examples 1-6. Compared to Comparative Examples 1-3, the alumina-zirconia composite coating and spherical modification have a synergistic effect. The composite coating layer inhibits the cyclic volume deformation of the active material, and the spherical modification reduces the generation of fine powder and optimizes the ion and electron transport paths. Compared to Comparative Example 4, the biodegradable cross-linked polyurethane binder of this application constructs a three-dimensional network, promotes lithium-ion transport, and reduces interfacial impedance, with performance significantly superior to traditional PTFE binders. The electrochemical performance of Examples 2-4 decreased to varying degrees with adjustments in coating amount, binder ratio, and shear temperature, verifying that the process parameters of Example 1 are optimal. In Example 5, polypropylene glycol was used for spherical modification, but the particle rounding effect was not as good as that of polyethylene glycol. The powder is prone to fine powder formation, leading to poor performance. The compaction density is slightly lower than the optimal range. Although the electrochemical performance decreases with decreasing compaction density, it is still significantly better than Comparative Example 1, indicating that composite coating combined with polypropylene glycol spheroidization modification can still effectively improve the electrochemical performance of lithium iron phosphate. Comparative Examples 5 and 6 only have single oxide coatings, and the coating layer is difficult to balance toughness and hardness, is prone to cracking, and has weaker cycle stability than aluminum-zirconium composite coating. Combining the film physical parameters, the thickness, porosity, and compaction density of the self-supporting electrode film in Example 1 are all within the optimal range. After the process conditions of Examples 2 to 4 deviated from the optimal parameters, the compaction density decreased and the porosity increased. All comparative examples lacked core modification methods or special binders, resulting in insufficient film density of the powder and a compaction density of less than 3.7 g / cm³. 3The lower limit proves that the proposed method can stably prepare dry self-supporting electrode films with high compaction, uniform structure and excellent electrochemical performance.

[0126] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0127] The above embodiments merely illustrate several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A method for preparing a positive electrode active material, characterized in that, Includes the following steps: A precursor solution is provided, the precursor solution comprising an aluminum salt and a zirconium salt; Lithium iron phosphate is mixed with the precursor solution and dried to prepare a pretreated material, wherein the total mass of aluminum and zirconium in the precursor solution accounts for 0.6% to 1.8% of the mass of lithium iron phosphate. The pretreated material is mixed with a spherical modifier, and then ground and sintered to prepare a positive electrode active material.

2. The method for preparing the positive electrode active material as described in claim 1, characterized in that, One or more of the following conditions must be met: (1) The molar ratio of aluminum to zirconium in the precursor solution is (1.5~2.5):1; (2) The spherical modifier includes one or more of polyethylene glycol, polypropylene glycol, and polyethylene wax; (3) The mass of the spherical modifier is 1% to 5% of the mass of the lithium iron phosphate; (4) The grinding speed is 2000 r / min~3000 r / min; (5) The grinding time is 2 h to 6 h; (6) The sintering temperature is 600 ℃~700 ℃; (7) The sintering time is 4 h to 8 h; (8) The aluminum salt includes one or more of aluminum nitrate, aluminum chloride, aluminum sulfate, and aluminum acetate; (9) The zircon salt includes one or more of zirconium nitrate, zirconium chloride, zirconium oxychloride and zirconium acetate.

3. A positive electrode active material, characterized in that, It is prepared according to the preparation method of the positive electrode active material according to claim 1 or 2.

4. A method for preparing a self-supporting electrode film, characterized in that, Includes the following steps: A dry powder mixture is prepared by mixing the positive electrode active material, polyurethane binder, and conductive agent as described in claim 3. The dry powder mixture is subjected to shearing and at least two pressing processes to prepare the self-supporting electrode film; The polyurethane adhesive is a cross-linked product of polyol and aliphatic polyisocyanate trimer.

5. The method for preparing the self-supporting electrode film as described in claim 4, characterized in that, One or more of the following conditions must be met: (1) The mass ratio of the active material, the polyurethane adhesive and the conductive agent is (92~96):(1~3):(2~5); (2) The conductive agent includes one or both of graphene and Super P; (3) The shearing temperature is 50 ℃~90 ℃; (4) The cutting time is 8 min to 12 min; (5) The shearing speed is 600 r / min to 1800 r / min; (6) The pressure of the first pressing is 80 MPa~120 MPa; (7) The temperature for the first pressing is 20 ℃~30 ℃; (8) The pressure of the second pressing is 150 MPa~180 MPa; (9) The temperature for the second pressing is 80 ℃~100 ℃; (10) The polyol includes one or both of polyether polyol and polyester polyol; (11) The aliphatic polyisocyanate trimer includes one or both of hexamethylene diisocyanate trimer and isophorone diisocyanate trimer; (12) The polyol and the aliphatic polyisocyanate trimer are mixed and heated to 70 ℃~90 ℃ to prepare the polyurethane adhesive; (13) The mass ratio of the polyol to the aliphatic polyisocyanate trimer is (85~92):(8~15).

6. A self-supporting electrode film, characterized in that, It is prepared according to the method for preparing the self-supporting electrode film according to claim 4 or 5.

7. The self-supporting electrode film as described in claim 6, characterized in that, The self-supporting electrode film satisfies one or more of the following conditions: (1) Thickness is 60 μm~180 μm; (2) Porosity is 35%~45%; (3) The compacted density is 3.7~4.0 g / cm³. 3 .

8. A positive electrode, characterized in that, It includes a current collector and a self-supporting electrode film as described in claim 6 or 7 disposed on one or both surfaces of the current collector.

9. A battery, characterized in that, Includes the positive electrode as described in claim 8.

10. An electrical device, characterized in that, Includes the battery as described in claim 9.